Effects of AI Image Generator Application on Student Cognitive Load in Design Studies - Wardono, Prabu; Aulia, Afina Nisa; Fahmi, Hasanul; Williem, Williem; Hastuti, Rani Puji (President University, 2024)
AI image generator applications have been widely developed for various purposes in the process of creating fine arts and designs. One of them, OpenArt, provides a facility to develop sketch images into realistic images. This study aims to examine the effect of using this facility on students' mental burden in presenting ideas into realistic chair designs. Fourteen interior design students were involved in this study. The experimental method was used, where they were asked to work on the design of a lounge chair through the stages of sketching manually and with OpenArt. From the two steps of work before and after using this AI application, students were asked to fill out a questionnaire regarding the mental burden they felt. With descriptive data analysis, the experiment showed that OpenArt had a positive effect in helping to reduce students' mental burden in translating ideas into realistic images of chair designs. From these results, it can be concluded that this AI application is considered useful for the design learning process, especially in helping students substantially realize their original ideas without having to be burdened by the mind to work on technical visualization matters alone.